NEGOTIATING BETWEEN SHARIA AND MEDICAL PRACTICE: An maqashid Analysis of Khashyat al-Imlāq as a Motive for Misoprostol Use in Indonesian Muslim Households - hendry hendri mania; Nofiardi Nofiardi (Malang Prodi. Ahwal Al-Syakhsiyyah, IAI Al-Qolam, 2025)
The use of misoprostol (miso) as an abortion drug has sparked ethical, medical, and legal debates. On the one hand, this drug has important medical functions, such as treating miscarriages, postpartum hemorrhages, and life-threatening emergencies in mothers. However, on the other hand, miso is often misused for illegal abortions. This article aims to examine the position of miso in the perspective of contemporary Islamic law through the maqāṣid al-syarī‘ah approach. The research was conducted using a qualitative method based on a literature study, with primary sources from the Qur'an, hadith, classical fiqh books, and contemporary fatwas from Majma' al-Fiqh al-Islami and the Indonesian Ulema Council (MUI). The results of the study show that the use of miso is permissible if there are sharia and medical reasons of emergency, such as saving the life of the mother or a fetus that is already dead, provided that the pregnancy is less than 120 days old. Conversely, the use of miso for illegal abortion without an emergency reason is considered haram, as it contradicts the principles of ḥifẓ al-nafs and ḥifẓ al-nasl. In conclusion, contemporary Islamic law affirms that the use of misoprostol must be subject to maqāṣid al-syarī‘ah, with strict medical supervision and regulation, in order to protect life and preserve offspring.